Branding in a multichannel retail environment: Online stores vs app stores and the effect of product type. Issue 4 (6th November 2017) - Rezaei, Sajad; Valaei, Naser
Abstract : Purpose: The purpose of this paper is to investigate the structural relationship between online brand equity, brand experience, brand attitude, and brand attachment while considering the moderating effect of store type (online stores vs app stores) and product type. Design/methodology/approach: A total of 459 completed online questionnaires were collected from experienced online ( n =254) and app shoppers ( n =205) to empirically test the proposed model. Partial least squares path modeling approach, a variance-based structural equation modeling, was performed to evaluate the measurement and the structural model. Findings: The study's empirical investigation validates the proposed model and implies that online brand equity, brand experience, and brand attitude explain 66 percent of variances in brand attachment. Partial least square-multi group analysis reveals that the type of store and product type are moderators to all the proposed relationships except the hypothesis on the relationship between online brand equity and brand attachment. Originality/value: With the tremendous advancement of information technology that enables firms to deploy multichannel strategy in their core business activities, the role of brand in a multichannel retail environment has been ignored. This study is among several attempts to examine the role of brand among consumers experienced with online and app stores. The practical implications and limitation are discussed.